Are Happier People Better Citizens? - Cahit Guven (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper presents evidence on causal influence of happiness on social capital and trust using German Socio-Economic Panel. Exploiting the unexplained cross-sectional variation in individual happiness (residuals) in 1984 to eliminate the endogeneity problem, the paper finds that happier people trust others more, and importantly, help create more social capital. Specifically, they have a higher desire to vote, perform more volunteer work, and more frequently participate in public activities. They also have a higher respect for law and order, hold more association memberships, are more attached to their neighborhood, and extend more help to others. Residual happiness appears to be an indicator of optimism, and has an inverse U-shaped relationship with social capital measures. The findings also suggest that the relationship between happiness and social capital strengthened in the world in the last decade.
Keywords: D3; O12; Z13; 330; happiness; trust; social capital; optimism